Pengaruh Relationship Quality terhadap Customer Loyalty (Survei pada Membership ISP First Media di Indonesia - Bambang Widjajanta; Ferany Nur Amalia Andini; Puspo Dewi Dirgantari (Journal of Business Management Education (JBME), 2023)
This study aims to obtain an overview and influence of relationship quality on ISP First Media customer loyalty survey on ISP First Media membership in Indonesia. This research uses descriptive and verifiative methods with a quantitative approach. The population in this study amounted to 16,300 people with a sample of 200 respondents who joined the first media user community facebook forum using simple random sampling techniques. The data is processed statistically by the Structural Equation Modeling (SEM) method. The findings of this study found that relationship quality has a significant influence on customer loyalty, this is indicated by a large critical ratio value that is greater than the minimum meaning that there is a positive and significant influence between relationship quality variables on customer loyalty simultaneously. The statement can be concluded that the better the relationship quality built by the company, the higher the level of customer loyalty felt by customers to the company. The result of the contribution given by the highest relationship quality variable in forming customer loyalty is the satisfaction dimension and the lowest in forming customer loyalty is trust.